2018
DOI: 10.3390/antiox7110154
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activities of Dialium indum L. Fruit and Gas Chromatography-Mass Spectrometry (GC-MS) of the Active Fractions

Abstract: The fruit of Dialium indum L. (Fabaceae) is one of the edible wild fruits native to Southeast Asia. The mesocarp is consumed as sweets while the exocarp and seed are regarded as waste. This study aimed to evaluate the antioxidant activities of the fruit by using four assays, which measure its capabilities in reducing phosphomolybdic-phosphotungstic acid reagents, neocuproine, 2,2-diphenyl-picrylhydrazyl (DPPH), and inhibiting linoleic acid peroxidation. The active fractions were then analyzed by gas chromatogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 48 publications
1
9
0
2
Order By: Relevance
“…The observed bioactivities of O. ficus-indica extracts were probably attributed to its polyphenolic content, especially to piscidic acid, eucomic acid, isorhamnetin derivatives, and rutin [31]. Moreover, Osman et al [32] identified by GC-MS the polyphenols of Dialium indum L. fruit and assessed in vitro their antioxidant properties. D. indum is native to Southeast Asia and its fruit is edible [32].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The observed bioactivities of O. ficus-indica extracts were probably attributed to its polyphenolic content, especially to piscidic acid, eucomic acid, isorhamnetin derivatives, and rutin [31]. Moreover, Osman et al [32] identified by GC-MS the polyphenols of Dialium indum L. fruit and assessed in vitro their antioxidant properties. D. indum is native to Southeast Asia and its fruit is edible [32].…”
mentioning
confidence: 99%
“…Moreover, Osman et al [32] identified by GC-MS the polyphenols of Dialium indum L. fruit and assessed in vitro their antioxidant properties. D. indum is native to Southeast Asia and its fruit is edible [32]. The results showed that the D. indum fruit contains phenolics, amino acids, saccharides, fatty acids, sesquiterpene, polyols, and dicarboxylic acids [32].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison with some species of the genus Dialium, this activity appears to be much greater. Indeed, the antioxidant activity on DPPH, expressed as IC50 in μg / mL, of several species of the genus Dialium is reported in the literature, D. indum, 181.6 ± 0.4 [33,34], D. guineense, 50.23 ± 0.15 [35], D. corbisieri, 14.44 ± 0.12 and D. gossweileri, > 500 [36], D. cochinchinensis, 65.01 ± 0.12 [37]. This interesting antioxidant activity observed in D. angolense would be linked to the presence of phenolic compounds mainly flavonoids, identified and quantified within the plant during this study (table 2), as well as several previous studies which testify to the antioxidant activity of flavonoids [38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, GC methods for the determination of polyphenols rely on derivatization procedures to reduce the polarity of analytes. In this regard, silylation has been successfully applied to the identification and quantification of phenolic compounds in plant and fruit extracts [66][67][68][69].…”
Section: Chromatographic Methodsmentioning
confidence: 99%